Intestinal Obstruction in Pregnancy: A Case Report. (6th February 2013) - Rauff, Shakina; Chang, Stephen Kin Yong; Tan, Eng Kien
Abstract : Background . Intestinal obstruction in pregnancy is uncommon. The condition is associated with significant maternal and fetal mortality. The delay in diagnosis is due to nonspecific symptoms and a disinclination to carry out radiologic investigations in pregnancy. Case . A 39-year-old lady at 32 weeks of gestation presented with abdominal pain and nausea. Her symptoms worsened during admission. A computed tomography (CT) scan showed dilated small bowel loops suggestive of intestinal obstruction. She eventually underwent a laparotomy as conservative measures failed. Conclusion . A high index of clinical suspicion is required to diagnose intestinal obstruction in pregnancy. Prompt diagnosis should be made and the appropriate treatment instituted. Surgical intervention should be performed if necessary as further delay only results in increased morbidity and mortality.